PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PT BPR PEDUNGAN - Andika Pramana Putra, I Kadek; Subudi, Made (E-Jurnal Manajemen, 2015)
The purpose of research to determine the effect of transformational leadership style and environment physical work simultaneously and partially on the performance of employees, and test variables dominant influence on employee performance. This research was conducted at PT. RB Pedungan with multiple linear regression analysis technique. Population is the whole subject of research as many as 90 employees number of samples obtained by using census method as much as 90 respondents. Based on the analysis concluded that the transformational leadership style and environment physical work it has positive and significant effect simultaneously and partially on the performance of employees. Transformational leadership style is the variable that most affects the performance of employees of PT. RB Pedungan.
Keywords: Performance, Transformational Leadership Style, Environment Physical Work